Material Design and Surface/Interface Engineering of Photoelectrodes for Solar Water Splitting. Issue 4 (8th March 2021) - Hu, Yingfei; Huang, Huiting; Feng, Jianyong; Wang, Wei; Guan, Hangmin; Li, Zhaosheng; Zou, Zhigang
Abstract : Photoelectrochemical (PEC) water splitting can convert solar energy into clean and renewable hydrogen energy, showing a promising application prospect. However, large‐scale implementation of PEC water splitting is now hampered by insufficient solar‐to‐hydrogen conversion efficiency, which requires the development of high‐performance photoelectrodes. Key processes that determine the water splitting performance of photoelectrodes are the light absorption, separation, and transport efficiency of photogenerated electrons and holes and the surface reaction of water oxidation/reduction. Concerning these three key processes, various material design and surface/interface engineering strategies have been explored to improve the performance of photoelectrodes. Herein, these strategies for photoelectrode optimization of the past decades are summarized and discussed in terms of micro‐ and nanostructuring, heterojunction construction, element doping, surface passivation, plasmonic metal coating, and electrocatalyst modification. Special attention is given to how these strategies play their roles in improving the performance of photoelectrodes, based on which it is hoped light is shed on the design principles and modification routes for high‐performance photoelectrodes. Abstract : Material design and surface/interface engineering strategies for optimizing the performance of photoelectrodes are summarized, by considering the recombination paths of charge carriers during photoelectrochemical water splitting. These strategies for photoelectrodes are classified into six parts, including micro‐ and nanostructuring, heterojunction construction, element doping, surface passivation, plasmonic metal coating, and electrocatalyst modification.